Selección de un sistema para vertebroplastia aplicando un proceso analítico jerarquizado - Márquez Miranda, Mario; Ferreyro Irigoyen, Roque; Mendoza Jasso, Álvaro J. (Revista Mexicana de Ingenieria Biomedica, 2005)
This work illustrates an application of a multi-criteria decision methodology, known as the Analytical Hierarchy Process (AHP), with the aim of selecting a percutaneous vertebroplasty system, in order to guarantee a suitable and practical solution to a problem in biomedical engineering. This process of AHP is about assigning relative “weights” to those different alternatives when solving a specific problem, this being influenced by objective and subjective criteria, which are originated by the individuals participating in solving the problem; in considering the last, a better solution for a vertebroplasty system is arrived at, allowing to make decisions with high probability of success. Two complex problems related with vertebroplasty are taken into account: on the one hand, the capacity of injecting a biomaterial, the polymethyl-methacrylate (PMMA), in the vertebral spongy bone; on the other hand, to set apart the physician to a safe distance from the system to avoid over-exposure to ionizing radiation. Other criteria like ergonomics, lifetime and price are examined.